2017
DOI: 10.1002/cpbi.37
|View full text |Cite
|
Sign up to set email alerts
|

Protein 3D Structure and Electron Microscopy Map Retrieval Using 3D‐SURFER2.0 and EM‐SURFER

Abstract: With the rapid growth of solved protein structures stored in the Protein Data Bank (PDB) and in the Electron Microscopy Data Bank (EMDB), it is essential to develop tools to perform real-time structure similarity searches against the entire structure database. Since conventional structure alignment methods need to sample different orientations of proteins in the three-dimensional space, they are time-consuming and unsuitable for rapid, real-time database searches. To this end, we have developed 3D-SURFER and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…We further compared the performance of VESPER using the DOT score and CC with three existing methods, gmfit and fitmap, and EM-SURFER that uses 3DZDs for the map shape search 10 , 14 . gmfit was run with 20 GDFs, which is the setting for map superimposition in the Omokage map search web server where gmfit was used 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further compared the performance of VESPER using the DOT score and CC with three existing methods, gmfit and fitmap, and EM-SURFER that uses 3DZDs for the map shape search 10 , 14 . gmfit was run with 20 GDFs, which is the setting for map superimposition in the Omokage map search web server where gmfit was used 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Then, from each of the randomly generated placements, local optimization is performed to maximize the correlation between two maps. Previously, we have developed EM-SURFER, a web-based tool for real-time global matching and database search for EM maps 10 , 14 . In EM-SURFER, we used 3D zernike descriptors (3DZD) for the efficient comparison of EM map isosurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that 3DZD can distinguish proteins of different folds even at low resolution of 15 Å. A web-based platform for comparing cryo-EM maps was also developed by the same group (Esquivel-Rodríguez et al, 2015 ; Han et al, 2017 ). A similar method utilized 3D Zernike moments to search a database of protein structures for matching protein structures to a cryo-EM map (Yin and Dokholyan, 2011 ).…”
Section: Application Of Shape Similarity Methods In Drug Discoverymentioning
confidence: 99%
“…The 3DZD files of the single-chain and the complex datasets are made available at S1 Data. 3DZD can be also computed for PDB files at the benchmark page of 3D-SURFER (http://kiharalab.org/3d-surfer/batch.php) [25,38].…”
Section: Methodsmentioning
confidence: 99%
“…Protein surface shapes were represented with 3D Zernike Descriptors (3DZD), mathematical moment-based invariants of 3D functions [23]. 3DZD has been demonstrated efficient for various biomolecular structure comparisons [24], including comparisons of EM maps [25]. Another critical difference between the current study and the previous works is that we analyzed protein complexes in comparison with single proteins.…”
Section: Introductionmentioning
confidence: 99%